\(\displaystyle{3}{x}-{3}={10}\)

\(\displaystyle{3}{x}={13}\)

\(\displaystyle{x}=\frac{{13}}{{3}}\)

\(\displaystyle{3}{x}={13}\)

\(\displaystyle{x}=\frac{{13}}{{3}}\)

Question

asked 2021-08-08

Identify whether each phrase is an expression, inequality, or equation.

\(\displaystyle-{10}={d}\)

\(\displaystyle{7}{f}^{{2}}\)

\(\displaystyle{8}{>}{h}\)

\(\displaystyle-{10}={d}\)

\(\displaystyle{7}{f}^{{2}}\)

\(\displaystyle{8}{>}{h}\)

asked 2021-08-13

The sum of the coefficients of (3x−2y)10 is
(A)1, (B),1024,(C)58.025,(D)59.049,(E)9,765,625.

asked 2021-08-08

y=x+6

Find y when x is: 0. 3. 5. 8.

Find y when x is: 0. 3. 5. 8.

asked 2021-08-14

Solve inequality, please: \(\displaystyle\frac{{{3}–{x}}}{{{x}+{5}}}\ge{1}\)